2016
DOI: 10.2147/ott.s99428
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of vitamin D receptor gene TaqI susceptibility of prostate cancer: a meta-analysis

Abstract: ObjectiveMany studies have investigated the association of the vitamin D receptor gene TaqI polymorphism with prostate cancer (PCa) risk. However, the evidence is inadequate to draw robust conclusions. To shed light on these inconclusive findings, we conducted a meta-analysis.Materials and methodsWe searched PubMed for eligible articles. The relevant data were abstracted by two independent reviewers with the Stata 11.0 software.ResultsA total of 27 studies were included. The pooled outcomes indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Furthermore, a recent meta-analysis of 19 prospective cohort or nested case-control studies suggested per 10 ng/ml increment in circulating 25[OH]D concentration, the risk of prostate cancer was approximately 4 % elevated [64]. Moreover, recent meta-analyses found the association between some race-related vitamin D receptors (VDR) polymorphisms (TaqI, FokI, Cdx2, ApaI, BsmI) and an increased risk of prostate cancer [65][66][67]. It should be noted that the seasonal variation might also affect the association found between the vitamin D and prostate cancer [68], since the sun exposure is the most important source regulator of serum vitamin D [69].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis of 19 prospective cohort or nested case-control studies suggested per 10 ng/ml increment in circulating 25[OH]D concentration, the risk of prostate cancer was approximately 4 % elevated [64]. Moreover, recent meta-analyses found the association between some race-related vitamin D receptors (VDR) polymorphisms (TaqI, FokI, Cdx2, ApaI, BsmI) and an increased risk of prostate cancer [65][66][67]. It should be noted that the seasonal variation might also affect the association found between the vitamin D and prostate cancer [68], since the sun exposure is the most important source regulator of serum vitamin D [69].…”
Section: Discussionmentioning
confidence: 99%
“…Aassociation between a significantly increased estimated chance of PSA <10 ng/ml with G allele (BsmI) and 9.75-fold increased chance of patients with prostate cancer having a lower PSA level with GG/GG genotype (BsmI/ApaI) was also found. Recently, various metaanalysis and case-control studies have been conducted to find a relation between VDR polymorphism (TaqI, FokI, Cdx2, ApaI, BsmI, rs731236, rs7975232, rs731236, rs1544410, rs3782905, rs1544410, and rs2239185) and risk of prostate cancer (11,13,18,22,(41)(42)(43)(44). VDR polymorphism FolkI, Cdx2, and ApaI were not found to have any association with an increased risk of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…For instance, the CDX2 polymorphism (SNP -rs11568820) of the VDR gene has been associated with cancer susceptibility amid varied results. Various researchers have conducted the meta-analysis to establish the viable association between VDR polymorphism and cancer risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A meta-analysis including 25 separate studies totaling 34,018 individuals published prior to March 2015 for CDX2 polymorphism association with cancer conducted by Dai et al demonstrated that in the homozygous model, CDX2 mutations were significantly associated with an increased cancer risk of colorectal and ovarian cancer, particularly in AfricanAmerican but not in Caucasians or Asians (10).…”
mentioning
confidence: 99%
“…However, these results have been disputable [ 20 22 ]. Previous meta-analyses were reported by Yin et al in 2009, Fei et al in 2016 and Liu et al in 2017 [ 10 , 23 , 24 ], in which the number of included studies was 23, 27 and 8, respectively. However, some new data was reported, which is not consistent with the results of the former three studies [ 17 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference might be due to under-power for individual study. Moreover, previous meta-analyses [ 10 , 23 , 24 ] seem to be outdated since new data appeared [ 17 , 25 27 ]. Therefore, we conduct this meta-analysis to get more accurate results.…”
Section: Introductionmentioning
confidence: 99%